The Future of UK Universities’ Transnational Education Engagement - Ilieva, Janet; Tsiligiris, Vangelis (International Higher Education, 2023)
Transnational education (TNE) has become a core activity for many UK higher education institutions, and supply-side and demand-side factors continue to support its growth. TNE lifecycle starts with filling the gaps in the supply of local higher education before its focus shifts to diversifying local provision, enhancing its quality and developing its capacity in niche subject areas. As a result, TNE generates substantial local impact and explicitly responds to the sustainable development agenda.